Small World: Collisions Among Attackers in a Finite Population - Herley, Cormac (WEIS, 2013)
The Internet is large, but it is finite. We examine the case of several attackers seeking victims in a large population where there is some prior statistic indicating likely viablility. We show that collisions reduce attacker gains: the sum of what several attackers can extract is always less than what a single attacker would extract alone. The problem gets worse as the density of victims in the population decreases.